Implementación de un aula online y su incidencia en la modalidad de estudio virtual de las alumnas de 8vo semestre de Secretariado Ejecutivo Bilingüe - Moreria Ruiz, Suany Sadith (2020)
The objective of this research is to determine the incidence of the implementation of an online classroom in the virtual study modality of the students of the 8th Semester of the Bilingual Executive Secretariat of the Technical University of Babahoyo. It has an exploratory and descriptive type of research. The study group was made up of sixteen (16) students from the 8th semester of the Bilingual Executive Secretariat Career, which symbolizes 100% of the study population, for data collection a survey was applied to the sixteen (16) students, made up of ten (10) questions, questions that determined the comfort that students feel when implementing an online classroom as a means of acquiring knowledge. The results obtained when faced with the question of whether the group of students has knowledge about what an online classroom is, was 65% of the sample knows what an online classroom is, while 29% agree and 6% agree. disagreement, it can be deduced that the knowledge about the online classroom is not null, but rather favorable, which makes the virtual study modality more bearable.